Neural Monitoring of the External Branch of the Superior Laryngeal Nerve During Transoral Thyroidectomy. (17th July 2020) - Ji, Yong Bae; Jeong, Jin Hyeok; Wu, Che‐Wei; Chiang, Feng‐Yu; Tae, Kyung
Abstract : Objectives/Hypothesis: There is no study regarding intraoperative neural monitoring (IONM) of the external branch of the superior laryngeal nerve (EBSLN) during transoral thyroidectomy. The objective of this study was to evaluate the feasibility and success rate of electrical identification of the EBSLN during transoral robotic or endoscopic thyroidectomy. Study Design: Case series study. Methods: We studied a cohort of 76 patients (87 nerves at risk, (NARs)) who underwent transoral robotic or endoscopic thyroidectomy and simultaneous intermittent IONM between July 2017 and May 2019. We performed the standard IONM procedure plus routine neural monitoring of the EBSLN. IONM and surgical outcome data were prospectively collected. Results: Sixty‐one patients underwent the robotic procedure, and 15 patients underwent the endoscopic procedure. Thirty‐seven external branches of the superior laryngeal nerves at risk (42.5%) were electrically identified using electromyography signals (31 NARs, 35.6%) or cricothyroid muscle twitches (6 NARs, 6.9%). The mean pre‐(S1) and post‐dissection (S2) amplitudes of the EBSLN were 372 ± 147 and 351 ± 159 μV, respectively. The identification rates were not different between the robotic and endoscopic procedures. In comparing the early 20 NARs (18 patients) and the later 67 NARs (58 patients), the identification rate was higher in the later cases, although the difference was not statistically significant (25.0% vs. 47.8%, P = .079). Conclusion: IONM of the EBSLN is feasible and useful in identifying and preserving the nerve during transoral thyroidectomy, although the identification rate of the nerve is relatively low. Level of Evidence: 4 Laryngoscope, 131:E671–E676, 2021